Privalomasis egzempliorius Lietuvoje 194S-1992 m. - Bagušytė, Ringailė (Knygotyra, 1999)
The article describes in detail the development of legal deposit in Lithuania from 1945 to 1992, with a major focus on the documents regulating legal deposit and the control methods applied to the delivery of these documents. A free obligatory copy, which was intended to fulfill the following major functions: archival, bibliographic, and statistical, and from 1945 to 1949 also librarian functions, was designated to the Bibliographic Centre - Books Palace from the very first day of its establishment, i.e., March 29, 1945. The article describes the legislative documents of the Council of Ministers of Lithuania (1945, 1950, 1951, 1952, 1959). Starting in 1967, a system for the delivery of legal deposit was established in Lithuania. The documents regulating legal deposit were not changed often. Only in the late 1980s, with the changing social and political environment, did Lithuania start to seek the most optimal version (1987, 1989, 1990). The article, analyzing the documents regulating legal deposit, discusses in detail the types of components of the legal deposit and the number of legal deposits designated to the Books Palace, which was not always optimal. The article describes in detail the control methods used to analyze the comprehensiveness of the reception of legal deposit, with a major focus on the basic control methods for publication delivery, i.e., on-site inspection of books included in the orders of polygraphic enterprises and regular review of periodical publications’ card indexes. The article also presents additional control methods, such as the inspection of ledgers of monthly reports submitted by regional printing houses, publishing houses, and publishing organizations. It emphasizes that the monthly lists presented by Glavlit, which were subject to inspection until 1958, as well as the review of indexes of public bibliography publications issued by Union Books Palace, did not play a very significant role in the control of the comprehensiveness of legal deposit reception. The performance of the legal deposit system in Lithuania was determined by the USSR institutions. However, even while operating within the limits permitted by the Union Books Palace, the basic functions of legal deposit were fulfilled in the Lithuanian Bibliographic Centre, and the fundamentals for further activities, which continue in the Centre of Bibliography and Book Science of the M. Mažvydas National Library, were developed.